ANTARA EKSPEDISI SAINTIFIK DAN ANCAMAN EKONOMI KOLONIAL: LETUSAN GUNUNG DI PRIANGAN PADA PARUH PERTAMA ABAD KE-19 - Jaelani, Gani Ahmad; Febriani, Rima; Mawarrani, Ratna Erika (Paradigma: Jurnal Kajian Budaya, 2023)
This article focuses on the volcanic eruptions in Priangan, West Java, in the first half of the nineteenth century. Even though volcanic eruptions are natural occurrences, their impacts on human lives are viewed as historical events. While such disasters caused damage and misfortune to those directly affected, some people may also use them as a source of inspiration to seek knowledge. Moreover, eruptions occurring in an area were, to a certain extent, considered as a threat to the colonial authorities. Using contemporary news, official reports, and diaries, this research analyzes the relationship between natural events and its surrounding social and political landscapes. Such relationships are examined primarily to show that the eruptions might inspire the development of science while becoming a setting for human tragedy. It also examines how the colonial government responded to these catastrophic events within the framework of colonial political economy. Finally, this article argues that scientists and colonial administrators actually took several actions to ensure the continuity of colonialism through volcanic science and to maintain the availability of economic resources. In conclusion, the disasters that occurred in the colonial period did not only precipitate more scientific explorations but also provided another perspective on the dynamics of colonialism in the Dutch East-Indies.